Bangladesh Land Acquisition Diagnostic Review : Legal and Institutional Framework, Procedures and Practices - Analysis of the Challenges of and Proposals for Strengthening the Country’s Land Acquisition System - World Bank (Washington, DC, 2022)
Bangladesh has experienced a rapid pace of economic growth in the last two decades, with notable achievements across several social development parameters. To ensure sustained higher economic growth, the government of Bangladesh (GoB) aims to expand infrastructure related investment in the areas of strategic connectivity, industrialization, tourism development, and trade promotion, all of which require a significant amount of land. Age-old legal and institutional legacies and practices, issues pertaining to institutional capacity, and the lack of interoperability between departments involved in land administration make the overall land acquisition (LA) process extremely complicated and lengthy, with the scarcity of land making it even more challenging. The overall objective of the study was to assess the challenges and identify a mechanism for system strengthening and the scope of needed legal and institutional reform to improve the speed, accuracy, and accountability of the LA process. This report is presented in five chapters that discuss the study method, the analysis of the existing system and its challenges, measures to address the challenges, and the scope of possible legal and institutional reform. After introducing the study in this chapter, Chapter 2 discusses the country’s LA system and the process in practice. Chapter 3 describes the overall land administration in Bangladesh, including the method for transferring property rights, the creation and updating of khatians, and the complexity involved in the ownership decision process, one of the primary causes of delays in the payment of compensation. Chapter 4 presents the key challenges in the LA process, from the frustrations faced by IAs, who watch the timelines for their projects extended years longer than planned, to the worries and concerns of affected landowners waiting for compensation. Chapter 5 presents the proposals for improving and strengthening aspects of the LA process, including pertinent issues identified for possible land administration reform.